2019
DOI: 10.1021/acs.inorgchem.9b01316
|View full text |Cite
|
Sign up to set email alerts
|

Turning On the Near-Infrared Photoluminescence of Erbium Metallofullerenes by Covalent Modification

Abstract: The photoluminescence of lanthanide ions inside fullerenes is usually very weak due to the quenching effect of the fullerene cage. In the case of Er@C 82 , the near-infrared emission from the Er 3+ ion is completely quenched by the C 82 fullerene cage. It remains challenging to turn on the photoluminescence of Er@C 82 and other monometallofullerenes. In this work, we adopt a covalent modification strategy to alter the electronic structure of the fullerene cage for sensitizing the near-infrared emission of Er 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(83 citation statements)
references
References 31 publications
(54 reference statements)
4
79
0
Order By: Relevance
“…The fluorescence from Th- and U-based EMFs has been previously reported. , It is also reported that, after covalent modification, the nonfluorescent and triplet mono-EMFs Er 3+ @C 2 n 3– (2 n = 72, 76, and 82), possessing open-shell electronic structures and one unpaired electron on the cage, with small band gaps can generate the signals of near-IR photoluminescence . Considering the several similarities, we reasonably deduced that thermodynamically stable U@C 84 isomers might also produce possible photoluminescence properties via the chemical modification method.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The fluorescence from Th- and U-based EMFs has been previously reported. , It is also reported that, after covalent modification, the nonfluorescent and triplet mono-EMFs Er 3+ @C 2 n 3– (2 n = 72, 76, and 82), possessing open-shell electronic structures and one unpaired electron on the cage, with small band gaps can generate the signals of near-IR photoluminescence . Considering the several similarities, we reasonably deduced that thermodynamically stable U@C 84 isomers might also produce possible photoluminescence properties via the chemical modification method.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The situation can be changed if endohedral metal atoms have low-energy emitting states, and near-infrared lanthanide-based luminescence had been observed in Er-and Tm-based EMFs. 19,[43][44][45][46][47][48] Surprisingly, Y 3 N@C 80 was found to show unusually strong luminescence and long uorescence lifetimes, but the reasons for this unexpected behaviour rst remained unclear. 49,50 Recently we found that the strong photoemission of Y 3 N@C 80 is caused by the small singlet-triplet S 1 -T 1 gap of less than 0.1 eV, which enables thermally activated delayed uorescence (TADF) via thermal population of the emitting S 1 state from the T 1 "reservoir".…”
Section: Introductionmentioning
confidence: 99%
“…
Erbium metallofullerenes exhibit near-infrared photoluminescence from the Er 3+ ions, which has potential applications in telecommunications, optical devices and bioscience. In this manuscript, we report the construction of a supramolecular complex of metallofullerene Er 3 N@C 80 and cycloparaphenylene [12] CPP to adjust the near-infrared photoluminescence of Er 3 N@C 80 through host-guest interactions.Moreover, this supramolecular complex shows a multiwavelength luminescence property. Mass spectrometry, electrochemical measurements and proton NMR spectroscopy were used to characterize the structure of Er 3 N@C 80 ⊂[12]CPP.
…”
mentioning
confidence: 99%
“…The electrochemical results of Er 3 N@C 80 ⊂[12]CPP show the negatively shifted redox potentials compared to pristine Er 3 N@C 80 and the 1 H NMR signals of Er 3 N@C 80 ⊂[12]CPP shift upfield compared to pristine [12]CPP. More importantly, the photoluminescence spectra show that the [12] CPP nanoring can affect the near-infrared emission of encapsulated Er 3+ ions in Er 3 N@C 80 , with the characteristic emission peak of Er 3+ at 1.5 μm being broadened and enhanced in the Er 3 N@C 80 ⊂[12]CPP complex, while the fluorescence lifetime of Er 3+ also becomes longer after assembly formation. Furthermore, the Er 3 N@C 80 guest also can influence the photoluminescence property of [12]CPP, whose emission peaks exhibit a slight blue-shift in the Er 3 N@C 80 ⊂[12]CPP complex.…”
mentioning
confidence: 99%
See 1 more Smart Citation